Kitab Tafsir Al-Rawi - Juzu' 'Amma: Satu Analisis - Ab. Kadir, Muhd Najib; Ibrahim, Mazlan (Jurnal Usuluddin, 2002)
Al-Quran is the source of knowledge for all Muslim. They should learn and understand thoroughly the content of al-Quran and its teachings. Addressing the issue, the writer will analyze some of the Malay ulama's (scholars) views regarding their interpretation Quranic verses. The discussion in this article focuses mainly on Yusuf Rawa's "The Tafs'ir al-Rawi: Juzuk 'Amma" which has become the main reference for the majority of Muslim students in the understanding of the meaning of al-Quran. The writer divides the discussion into two aspects, namely, the background of the author and his method of writing.